أثر استخدام التوقيع الرقمي في العمليات المصرفية الالكترونية (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The purpose of this research is to identify the E-signing and its concept.Due to the increasing role and importance of the E-trade in may countries, as it provide many advantages over the traditional trade. We have to deal with may E-trade aspects and tools in which the E-signing is the most important. In this research we will deal: first with the article approach- E-signing definition, Digital signing, its mechanism, requirements, types and features. Second: the practical approach: It has been implemented according to a questionnaire contain many questions some of them are comma, other an specialized in research hypothesis and some concern the obstacles faced the application of E-signing. The questionnaires been distillated to the staff of the control Bank, Baghdad Bank and the Iraqi commercial Bank. The statistical Methods applied to test the questionnaire results through the analysis called (One Sample t-test) in which we arrived into a set of conclusions and recommendation.